1998
DOI: 10.1046/j.1365-2982.1998.00085.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of gastro‐oesophageal reflux in the ferret

Abstract: Transient lower oesophageal sphincter (LOS) relaxation is the major mechanism of gastro-oesophageal reflux in humans--an event unassociated with swallowing. Mechanisms involved in triggering transient LOS relaxation are poorly understood, and their further study requires a small animal model. In this study we aimed to establish methods for prolonged ambulant oesophageal manometry in ferrets, and to determine motor events associated with reflux episodes and their triggering by different gastric nutrient loads. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 27 publications
4
25
0
Order By: Relevance
“…This is unlikely to be a technical issue, as we have observed inhibition of all types of afferents in both species previously with peptide agonists such as galanin (49). It is conceivable that this difference between mice and ferrets reflects the inability of rodents to vomit and to exhibit gastroesophageal reflux, whereas ferrets like humans are able to vomit and do exhibit gastroesophageal reflux (11). Interestingly, it has been shown that ghrelin has antiemetic effects in the ferret (53) although its effect on ferret food intake has not been specifically evaluated.…”
Section: Discussionmentioning
confidence: 71%
“…This is unlikely to be a technical issue, as we have observed inhibition of all types of afferents in both species previously with peptide agonists such as galanin (49). It is conceivable that this difference between mice and ferrets reflects the inability of rodents to vomit and to exhibit gastroesophageal reflux, whereas ferrets like humans are able to vomit and do exhibit gastroesophageal reflux (11). Interestingly, it has been shown that ghrelin has antiemetic effects in the ferret (53) although its effect on ferret food intake has not been specifically evaluated.…”
Section: Discussionmentioning
confidence: 71%
“…The magnitude and duration of the lower oesophageal sphincter relaxation associated with this swallow is typical, and clearly very different from the transient lower oesophageal sphincter relaxation. mechanisms of reflux [51,52]. Mechanisms of reflux have also been described in humans of all ages down to premature infants of only six and a half months' gestational age [51,53,54].…”
Section: Lower Oesophageal Sphincter Dysfunctions Associated With Gasmentioning
confidence: 99%
“…Normally, a strong contraction of the crural diaphragm will prevent reflux during deep inspiration, straining or coughing [36, 37]. This contraction, which occurs faster than the increase of abdominal pressure [37], provides an active protection against straining-induced reflux, which is defective in case of a hiatal hernia [38]. In addition, a hiatal hernia may be associated with enhanced triggering of TLESRs [39].…”
Section: Hiatal Herniamentioning
confidence: 99%
“…A number of studies have shown delayed gastric emptying in patients with GERD [80,81,82,83,84,85]. In theory, delayed gastric emptying could lead to accumulation of a larger intragastric volume of solids and liquids leading to reflux [86] or the resultant gastric distension may provoke more TLESRs [36, 87, 88], possibly through activation of gastric mechanoreceptors [37,38,39, 89, 90]. On the other hand, several studies have failed to show a correlation between delayed gastric emptying and increased gastroesophageal reflux.…”
Section: Gastric Dysmotilitymentioning
confidence: 99%